Review of Ruppellia Wiedemann, 1830 (Diptera: Therevidae) in the Middle East - Badrawy, Haitham B. M.; Mohammad, Salwa K. (Zootaxa, 2011)
The Egyptian fauna of the genus Ruppellia Wiedemann, 1830 is revised based on new material from Egypt, Israel, Oman, Tunisia, United Arab Emirates (UAE) and Yemen and on reexamination of the types in Egyptian collections. We recognize two distinct species: Ruppellia semiflava Wiedemann, 1830 and Ruppellia thoracica (Macquart, 1840). Ruppellia pallida Kröber, 1929 and Ruppellia apicalis Kröber, 1929 (new name = subapicalis Lyneborg, 1983) are synonymized with R. semiflava based on examination of the female type specimen of the former and the male type specimen of the latter species. Also, Thereva nuda Loew, 1856 is removed from synonymy with R. semiflava and placed as a new synonym to R. thoracica. Cataclinoneurum alexandrinum (Becker, 1912) is confirmed as a synonym to R. thoracica after we obtained pictures of the types. Ruppellia semiflava is recorded in Oman, UAE and Yemen for the first time. Ruppellia is redefined based on the number of dorsocentral setae. Illustrations, key, specimens examined and distributions are given for each species, along with color images of type specimens.